The Criminal Sanction Policy Against Victims Of Criminal Activities In Household - Sekaring Dyah Ika Wulan; Sri Endah Wahyuningsih (Universitas Islam Sultan Agung, 2021)
The research objectives in this study are to: examine and analyze the policy of criminal sanctions against victims of domestic violence in the Law on the Elimination of Domestic Violence, to examine and analyze the constraints of criminal sanctions policies against victims of domestic violence, to examine and analyze the policy of criminal sanctions against victims of domestic violence in the future. This thesis uses a normative juridical approach, with a descriptive analytical research method. The data used are primary and secondary data which will be analyzed qualitatively. The research problems were analyzed using the theory of legal protection and the theory of justice. The results of the study conclude that acts of violence that occur in the household are also the same as other forms of crime in general, however, domestic violence has a special nature and characteristics that lie in the relationship between the perpetrator and the victim, as well as the ways of solving it. The obstacles to the policy of criminal sanctions against victims of domestic violence are: 1). The purpose of sentencing is not merely as a retaliation for the actions of the defendants in order to become a deterrent. 2). Weak corners of the basic idea of the double track system. 3). Weak legal sanctions given to domestic violence defendants. The Drafting Team of the Criminal Code has made a rating based on the gravity of criminal acts. This rating is divided into five levels using a semantic scale technique, from “very light” to “very serious” with a note that “very light” crimes are not subject to deprivation of liberty, while very serious crimes are crimes that are subject to deprivation of liberty/imprisonment for more than seven years.